A study of relation between primary open angle glaucoma and type II diabetes mellitus - Desai, Aditya; Patel, Dipak; Sapovadia, Avani; Mehta, Parin; Brahmbhatt, Jyotindra (International Journal of Research in Medical Sciences, 2018)
Background: Primary open angle glaucoma has been characterized by its adult onset, IOP >21mmHg at some point in the course of the disease, open angles on gonioscopy, glaucomatous visual field changes and glaucomatous optic nerve damage. POAG is a multi-factorial disease such as age, black race, positive family history, high myopia etc. Diabetes mellitus has also been considered as one of the risk factors, but no major study has been conducted to provide tangible proof. Methods: This cross sectional, case control study was conducted to determine whether diabetes stands as a risk factor in development of glaucoma. The selected patients were divided into 3 groups based on inclusion and exclusion criteria. They were subjected to complete ocular examination including gonioscopy and perimetry. Results: The 16 patients from 50 of the diabetic group (28%) were found to have POAG. The p value was <0.005 which was statistically significant. Also, no correlation was found between blood sugar and IOP levels in these patients. Conclusions: These data show a significant correlation between diabetes and glaucoma. Further studies are warranted to determine its actual role in pathogenesis of glaucoma.